Tiempos de cosecha sobre el valor nutritivo del forraje verde hidropónico de cebada - Aroni Quintanilla, Yovana (2024)
The aim of this study was to evaluate the effect of harvest days (16, 18, 20 and 22 after germination) on the nutritional value of hydroponic green forage (HGF) of barley in terms of chemical composition: dry matter (DM ), organic matter (OM), crude protein (CP), mineral matter (MM) and neutral detergent fibre (NDF), and the determination of the kinetic parameters of the in situ degradation of DM and CP, using three cattle with fistula rumen. The incubation times were: 0, 6, 12, 24, 48 and 72 hours. The DM and MM were similar (p>0.05) in the cultures, while the highest CP concentration was observed on day 16 and 18 (15.07 and 14.66%, respectively). NDF decreased linearly due to the effect of harvest days. The day factor quadratically influenced the degradation of the soluble fraction (SF) of the DM and PC, estimating 60 and 62.53% as maximum degradation of SF at 17 and 15 days of harvest, respectively. On the contrary, the potentially degradable fraction (PFD) of DM and CP decreased by 15.91 and 12.88% at 19 and 13 days of germination, respectively. The potential degradability of the DM was high and different on days 16 and 18, and with higher and similar values ​​in the effective degradability for the passage rates of 2, 5 and 8%/hour in relation to the other days. The same behaviour was recorded in the CP passage rates. The FVH of barley at 16 and 18 days after germination has a higher CP content, lower indigestible fractions of DM and CP and high effective degradability, which allows these crops to be classified as feeds of high nutritional quality that favour their use as a supplement for ruminants.